2017
DOI: 10.1515/humo-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

The development of tactical skills in U-14 and U-15 soccer players throughout a season: a comparative analysis

Abstract: Purpose. Players' tactical skills are crucial for a successful, high-standard career in soccer. Although recent studies propose and apply the analysis of young players' tactical skills through the understanding of their knowledge about tactical principles, no research has compared the development of these specific tactical skills throughout a soccer specific season in different youth academies. this article aimed to compare the development of tactical skills in U-14 and U-15 soccer players throughout a season.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In future research, it will be necessary to further develop a model of timely acquisition of tactical knowledge in water polo, as the acquisition and development of tactical skills in young athletes is different and non-linear, and the need for constant assessment during the training process is justified by age (de Castro Júnior et al, 2020;Praça et al, 2017). Following this research, the results could be incorporated into the training process and curricula for tactical training in water polo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future research, it will be necessary to further develop a model of timely acquisition of tactical knowledge in water polo, as the acquisition and development of tactical skills in young athletes is different and non-linear, and the need for constant assessment during the training process is justified by age (de Castro Júnior et al, 2020;Praça et al, 2017). Following this research, the results could be incorporated into the training process and curricula for tactical training in water polo.…”
Section: Discussionmentioning
confidence: 99%
“…Coaches and athletes have been clearly identified as having difficulty recognising tactical potential, an important construct in the assessment of tactical skills (Silva et al, 2023). The acquisition and development of tactical skills in young athletes is variable and non-linear, and the need for continuous assessment during the training process across age is warranted (Praça et al, 2017;de Castro Ribeiro et al, 2021). For the first time, a study identified and explained coaches' opinions on the optimal age for learning a set of 39 water polo technique elements (Hraste et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…As this appears to be a new finding, future studies should analyze how this variable is developed over time in a competitive season as a result of players’ tactical development. 39 It is argued that the increased ability to collectively maintain ball possession and higher positional stability allowed older athletes to search for more dangerous passing lanes in the offensive phase and protect the central corridor of the pitch when defending. Together, these two behaviors can explain the current results.…”
Section: Discussionmentioning
confidence: 99%
“…The age group of the present study is in the phase of the direction of the training process 21 , and did not fully develop their tactical, technical, physical and psychological abilities. Accordingly, studies have shown differences in the performance of athletes between different categories [22][23][24] , which evidence the need for hours of practice towards expertise and consequently a more specific performance regarding position functions. Also related to the teaching-learning-training process, in the age group of the present study, athletes evolve significantly throughout the season 24 , so the moment when the evaluation was performed may have influenced the observed results.…”
Section: Discussionmentioning
confidence: 99%